A novel ratiometric fluorescent probe for the detection of mitochondrial pH dynamics during cell damage. Issue 2 (14th November 2020) - Fu, Gaoqing; Yin, Guoxing; Niu, Tingting; Wu, Wei; Han, Hui; Chen, Haimin; Yin, Peng
Abstract : A sensitive fluorescent probe ( E )-4-(3-(benzo[ d ]thiazol-2-yl)-4-hydroxy-5-methylstyryl)-1-methylpyridin-1-ium iodide (HBTMP) for the monitoring of pH in mitochondria was rationally exploited. Abstract : A sensitive fluorescent probe ( E )-4-(3-(benzo[ d ]thiazol-2-yl)-4-hydroxy-5-methylstyryl)-1-methylpyridin-1-ium iodide (HBTMP) for the monitoring of pH in mitochondria was rationally exploited. This novel probe exhibited remarkable pH-dependent behavior in the linear range of 5.5–8.0, along with a p K a value of 6.829 ± 0.02627. A large Stokes shift of 205 nm was obtained. This fluorescent probe demonstrated good biocompatibility and high sensitivity for detecting the dynamic changes in mitochondrial pH in living cells and zebrafish. The results of the CCCP ( m -chlorophenyl hydrazone) treatment experiment indicated that the probe can effectively monitor changes in mitochondrial pH caused by cell damage.